Analisis Perbandingan Fungsionalitas dan Keluwesan antara Perplexity dan Phind.Com dalam Memenuhi Kebutuhan Belajar Mahasiswa di Lingkungan Perguruan Tinggi - Nurfadilah Syafiuddin; Andi Alimuddin Unde; Muh. Akbar (Syntax Corporation Indonesia, 2024)
This study aims to analyze the comparison of functionality and flexibility between Perplexity and Phind.com in meeting student communication needs in a university environment. In an increasingly advanced digital era, the use of artificial intelligence-based applications is very important to support the learning process and student communication. Perplexity is known for its fast and accurate search capabilities while Phind.com superior personalization and flexibility in the delivery of information. This research uses a mixture of qualitative and quantitative data collection and analysis methods. A survey was conducted among 200 students and semi-structured interviews were also conducted among 10 students at Hasanuddin University who had used the Perplexity application and Phind.com. Data collection techniques used in this research are questionnaires, interviews with informants who are considered competent and in accordance with the topics discussed. The results of this research show that Perplexity and Phind.com. has different functionality and flexibility in meeting student learning needs. In the case of researchers, Perplexity excels at providing access to quality and diverse learning materials and features that support independent learning. Meanwhile, Phind.com excels in providing an active discussion forum and learning community, as well as features that support collaboration and interaction between students. Both applications have their own advantages and disadvantages. The right application for students depends on their individual learning needs and learning style.